Mediating role of organizational attractiveness on the relationship between green recruitment and job pursuit intention among students of Universiti Teknologi Malaysia - Muhammad Hamza Khan (Taylor & Francis Group, 2020)
The purpose of this study was to investigate whether green recruitment practice attracts prospective candidates to join environmental responsible firms through organizational attractiveness. A total of 127 students from Universiti Teknologi Malaysia participated in the survey. SPSS version 23 was used to test the mediation model with the help of regression analysis. Results showed that green recruitment relates positively to job pursuit intention and organizational attractiveness partially mediates the relationship and students studying in universiti teknologi Malaysia have higher job pursuit intention towards environment responsible firms. Findings further highlight that green recruitment is a source of attracting potential candidates to pursue career in the green organizations and will allow practitioners to merge green human resource management with their traditional human resource policies to recruit quality candidates. Finally, by empirically providing positive outcomes this study adds to the body of literature in the field of green human resource management which is still at emerging stages.